Quality of life from the perspective of physical functioning in patients with rheumatoid arthritis - preliminary report - Anna Michalik; Monika Spratek (Journal of Education, Health and Sport, 2018)
Introduction: Rheumatoid arthritis is a chronic, inflammatory, progressive disease of connective tissue with an immunological basis. The quality of life of patients with RA is reduced due to progressive disability limiting the performance of basic everyday activities. Materials and methods: The research was carried out by means of a diagnostic survey, using a survey technique. The research tools included the HAQ questionnaire, the VAS scale and the survey questionnaire of own design. The research was conducted among 50 RA patients meeting the ACR and ELUAR classification criteria and with a positive RF result. Results: Patients suffering from rheumatoid arthritis encounter many limitations in everyday functioning. The higher level of HAQ was found in persons over 65, with primary and vocational education, living in towns/cities, with marital status: single, divorced, widowed. Conclusions: The severity of pain assessed by means of the VAS scale significantly affects the quality of life of patients with RA evaluated with the HAQ questionnaire. Socio-demographic factors, such as: age, education, place of residence, marital status, significantly influence the value of HAQ. Patients over 65, with primary and vocational education, living in towns/cities, with single marital status, showed a significantly higher level of HAQ. There exists a correlation between the duration of the disease and the HAQ and VAS values. The stronger the pain experienced by patients, the higher the level of disability affecting the value of HAQ.